CHARACTERISTICS AND OUTCOMES OF PATIENTS WITH CHRONIC MYELOGENOUS LEUKEMIA IN BLAST CRISIS - Sarwar, Sohail; Siddiqui, Neelam; Zafar, Waleed; Fasih, Sameer; Basit, Abdul; Hameed, Abdul (Journal of Ayub Medical College Abbottabad, 2015)
Background: Chronic myelogenous leukaemia (CML) is a hematopoietic stem cell disease with a relatively stable clinical course. Survival has increased with addition of Tyrosine Kinase inhibitors (TKI's). Its conversion into blast crises (BC) heralds an accelerated clinical course that is less responsive to treatment and has high mortality. Methods: Clinical records of 20 patients with CML who transformed to BC in two years between January 2012 and December 2013 were reviewed. Results: Out of total 240 patients, 20 (8.3%) transformed to blast crisis, among them 75% were males and 25% females. Mean age was 37.9 years (24-58 years) and 19 patients were positive for t (9; 22) (q34; q11) translocation at the time of transformation. The mean initial blood cell count was 204 (range: 33 to 526). Imatinib was offered in 76% of patients. The average duration between diagnosis and transformation to blast crises was 201 days (range: 24-333 days). Eight patients (40%) were transformed to acute myeloid leukaemia (AML) and 12 (60%) had acute lymphoblastic leukaemia (ALL). These patients were treated with standard AML/ALL type induction chemotherapy except one who died early. During the study period, 11 patients died. Median survival for whole group was 55 days. On bivariate and multivariate linear regression analyses mortality was not significantly associated with the duration between diagnosis and development of blast crises or the type of treatment received. Conclusion: Treatment of BC remains a challenge, particularly in under resourced areas where allogeneic hematopoietic stem cell transplantation (Allo-SCT) facility is sparse. Outcomes remain dismal in majority of these patients. Keywords: Chronic myelogenous leukaemia, Tyrosine Kinase inhibitors, Blast crises